The fluctuating velocity field of a forced planar impinging gas jet. Issue 9 (2nd September 2018) - Ritcey, Adam; McDermid, Joseph; Ziada, Samir
ABSTRACT: The fluctuating velocity field of a planar impinging gas jet is studied using particle image velocimetry, while anti-symmetrically forcing the jet column at the nozzle exit using planar synthetic jets. The jet exit velocity is set to  = 11 m/s providing a jet Reynolds number of, and the impingement distance is held constant at eight times the nozzle width W . Under forcing conditions near unstable frequencies, both the stream-wise and cross-stream fluctuating velocity fields of the jet have very different characteristics than that of the unforced jet. The fluctuating velocity fields reported here were also found to have qualitatively similar features to that of a high-speed self-excited impinging jet. For the highly periodic flow conditions tested, a triple decomposition, and a low order reconstruction of the fluctuating velocity field using proper orthogonal decomposition is employed. These methods allow for the extraction of the coherent velocity and turbulence fields from the forced planar impinging gas jet.